The insulin-like growth factor system and its receptors: A potential novel anticancer target - Colin R. Lindsay (Dove Medical Press, 2008)
Colin R. Lindsay1, T R Jeffry Evans1,21Beatson West of Scotland Cancer Centre, Glasgow, United Kingdom; 2University of Glasgow, CR-UK Beatson Laboratories, Garscube Estate, Glasgow, United KingdomAbstract: The current generation of novel anticancer therapies that are in preclinical and clinical development are based on exploiting our increasing understanding of the molecular and cellular basis of cancer development and progression. Accelerated rates of cell division and proliferation have been postulated to predispose to the development of malignant disease. The insulin-like growth factor (IGF) signaling system has an important physiological role in regulating cellular proliferation and apoptosis. This function has led to considerable interest in its relevance to neoplasia over the last decade. In this review, we give an overview of the IGF system physiology, discuss the epidemiological significance of IGF signaling and neoplasia, and review the preclinical and clinical studies in targeting IGF receptors as cancer therapies.Keywords: insulin, growth factor, IGF-1, clinical trials